1988
DOI: 10.1016/0014-5793(88)80919-0
|View full text |Cite
|
Sign up to set email alerts
|

Subpicosecond characterization of the optical properties of the primary electron donor and the mechanism of the initial electron transfer in Rhodobacter capsulatus reaction centers

Abstract: The optical difference spectrum of the excited primary electron donor, P*, in Rb. capsulatus reaction centers has been measured 600 fs after a 350‐fs flash at 870 nm. The spectrum is characterized by bleaching in the ground state absorption bands at 855 and 600 nm, and a weak featureless transient absorption in between. The lack of significant (if any) bleaching at 800 nm indicates that P does not contribute appreciable oscillator strength to the 800‐nm ground state absorption band. The conversion of P* to P+B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1988
1988
1992
1992

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 44 publications
(44 reference statements)
2
25
0
Order By: Relevance
“…wild type (10)(11)(12)(13)(14)(15)(16). Heterogeneities in the kinetics of the electrochromic band shift associated with charge separation have been observed recently for reaction centers of R. sphaeroides R-26 (22), but these authors reported that the kinetics of the stimulated emission were single exponential.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…wild type (10)(11)(12)(13)(14)(15)(16). Heterogeneities in the kinetics of the electrochromic band shift associated with charge separation have been observed recently for reaction centers of R. sphaeroides R-26 (22), but these authors reported that the kinetics of the stimulated emission were single exponential.…”
mentioning
confidence: 90%
“…The lower-exciton excited state of the dimer, P*, is the precursor of electron transport; the chargeseparated state P+H-is formed in 0.7-3.5 ps, depending on the species and temperature (10)(11)(12)(13)(14)(15)(16). Until now, femtosecond studies have not revealed any deviations from smoothly decaying functions in the kinetics of P*.…”
mentioning
confidence: 99%
“…We considered this same possibility in a more recent study on Rb. capsulatus RCs upon finding that the time constant measured near 785 nm appeared to be somewhat longer than the -3 ps observed at 800 nm and for the decay of P* stimulated emission (12).…”
Section: Methodsmentioning
confidence: 99%
“…Kinetics also have been measured at a few wavelengths near 800 nm in the recent studies of the P*-P+BPh-process, with the primary focus being a search for evidence for the possible transient reduction of the monomeric pigment BChlL (6,7,11,12). During the course of our previous investigations of electron transfer from BPhjL to QA, we examined the near-infrared (730-830 nm) region also, with the expectation of finding time constants that agreed with those measured via decay of the BPhL anion band.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of the State P+H" is generally accepted but there is presently debate over the existence of the intermediate P+B\ Measurements performed at 10K (Fleming et aly 1988;Breton et aly 1988) and with RC from the bacterium Rb. capsulatus (Kirmaier and Holten, 1988) have not detected a distinct radical pair before P+H -.…”
Section: Introductionmentioning
confidence: 99%